2017
DOI: 10.5530/pj.2018.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Total Flavonoid and Total Phenolic Content and Antioxidant Activity of Different Parts of Caesalpinia bonduc (L.) Roxb

Abstract: Background:Caesalpinia bonduc (L.) Roxb are traditionally used in Indonesia to treat various diseases, but still limited study about different part of this plant. Objective: The aim of this study was to screen the phytochemicals, to evaluate the total flavonoid and total phenolic contents as well as antioxidant activity of ethanol extract of root, stem, leaves, and seed kernel of C. bonduc. Methods: Each part of plant were extracted by reflux using 70% ethanol as the solvent for 2 h and repeated 3 times. Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 15 publications
3
135
2
7
Order By: Relevance
“…The ethanol was chosen in this study because its considered safer, and environmentally friendly compared to other solvents. Moreover, several studies have demonstrated higher antioxidant activity as well as total phenolic content when extracted with ethanol in Caesalpinia bonduc, 19 seagrass T. testidunum, 10 palm kernel-by product 14 and in black tea and mate tea. 20 Another significant influence in obtaining the phenolic content and antioxidant activity is the proportion of water in ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol was chosen in this study because its considered safer, and environmentally friendly compared to other solvents. Moreover, several studies have demonstrated higher antioxidant activity as well as total phenolic content when extracted with ethanol in Caesalpinia bonduc, 19 seagrass T. testidunum, 10 palm kernel-by product 14 and in black tea and mate tea. 20 Another significant influence in obtaining the phenolic content and antioxidant activity is the proportion of water in ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Total flavonoid content was measured using the aluminum chloride colorimetric assay, adapted from a previous protocol. 20 Aqueous FD and SD extracts at 20-500 mg/mL and the product or placebo product or different dilutions of standard quercetin solution (4.7-75.0 mg/ mL) (Aldrich, Germany) were added in 100 µL of 10% AlCl 3 (BDH PROLABO, Germany). Then, 100 µL of sodium acetate (1.0 mol/L) (Ajax Finechem Pty Ltd, Germany) was added to 2.8 mL of deionized water.…”
Section: Total Flavonoid Contentmentioning
confidence: 99%
“…All determinations were carried out in triplicates. The total phenolic content was expressed as the number of equivalents of gallic acid (GAE) [29,31].…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Blank was methanol. The absorption of the standard quercetin solution (20-100 μg/mL) in methanol was measured under the same conditions [29,31].…”
Section: Total Flavonoid Contentmentioning
confidence: 99%